Bilingual E-Book: A Platform to Promote Culinary Tourism from Palembang - Shahab, Aisyah; Hutagalung, Genta Ulina; Rohliah, Leni; Lutfiyatun, Eka; Pasya, Akhsan Fulki; Rohman, Fathur; Stefanus, Glorio Christmas (Samarinda State Polytechnic, 2024)
The culinary industry is one of the leading sectors in creative industries, with pempek from Palembang being a notable example. The increasing number of national and international events held in Palembang underscores the importance of promotion and marketing. In the era of Society 5.0, the use of digital and English-based promotional media is essential. This study employs research and development methods to describe the design and development of a bilingual e-flip book as a promotional tool for culinary tourism. The product is a digital promotional medium accessible via an Instagram link, featuring an attractively designed digital book with a red, black, and white color scheme. Each page includes images of products, prices, brief descriptions, facilities, ordering procedures, and payment methods in both Indonesian and English. The flip book effect simulates the experience of flipping through a real book. The product validation results from language experts (90) and design experts (88.63) yield an average score of 89.32, indicating high suitability. Public response to the bilingual e-flip book is very positive, with 69.2% agreeing it is highly efficient for obtaining information about products and facilities at culinary tourism destinations, 65.4% finding the information very accurate, and 71.8% considering it highly practical for promotional purposes.